Radio Frequency Ablation in Drug Resistant Chemotherapy-induced Peripheral Neuropathy: A Case Report and Review of Literature - Yadav, Naveen (Medknow Publications, 2010)
Chemotherapy-induced peripheral neuropathy (CIPN) is a frequently encountered complication. It can result from a host of agents. Various modalities of treatment have been advocated, of which a novel method is radio frequency ablation. A 63-year-old male, a case of carcinoma prostrate with bone metastases, presented with tingling and numbness in right upper limb. He was given morphine, gabapentin and later switched to pregabalin, but medications provided only minor relief. Initially he was given stellate ganglion block, then radiofrequency ablation of dorsal root ganglion was done, but it failed to provide complete relief. Pulsed radiofrequency ablation (PRF) was then done for 90 seconds; two cycles each in both ulnar and median nerve. After the procedure the patient showed improvement in symptoms within four to five hours and 80% relief in symptoms. We conclude that PRF can be used for the treatment of drug resistant CIPN.